PENGARUH STRUKTUR, BUDAYA, DAN LINGKUNGAN ORGANISASI TERHADAP DIMENSI MANAGERIAL ENTREPRENEURSHIP PADA PERUSAHAAN DAERAH SE-KALIMANTAN SELATAN - Syahdan, Saifhul Anuar; Santoso, Purbayu Budi (JURNAL BISNIS STRATEGI, 2004)
This study examines what structure, culture, and environment of organizational potentially influence to dimensions of managerial entrepreneurship in local government firm. Independent variables used inthis study are hierarchy, formalization, trust, mission, ethics, and legal constrains. These independent variables can increase customer satisfaction, reduce the level of red tape, and promoting the propensity for risk taking.Data of this study were taken from local government (Water Supply) from Kata dan Kabupaten in South Kalimantan. The questionnaires were administered to middle manager and low manager with response rate was 60% (182 out of 300). Data of this study are analyzed with multiple regression analysis to examine the variables hypothesized. The result of this study indicates that hierarchy, formalization, trust, mission, ethics, and legal constrains are statically significant and associated with customer satisfaction. The level of perceived red tape is relatively affected by hierarchy, trust, mission, and ethics. The result implies that risk taking behavior is likely to be affected by hierarchy, trust, and legal constrains. Future research is expected to add other factors that influencemanagerial entrepreneurship dimensions such as centralization and specialization. Then managerial entrepreneurship dimensions can be added such as employees' empowerment and cost efficiency.